2013
DOI: 10.1638/2012-0071r.1
|View full text |Cite
|
Sign up to set email alerts
|

INTESTINAL AND CLOACAL STRICTURES IN FREE-RANGING AND AQUARIUM-MAINTAINED GREEN SEA TURTLES (CHELONIA MYDAS)

Abstract: Intestinal or cloacal strictures that resulted in intestinal obstruction were diagnosed in six green sea turtles (Chelonia mydas) from three rehabilitation facilities and two zoologic parks. The etiologies of the strictures were unknown in these cases. It is likely that anatomic adaptations of the gastrointestinal tract unique to the green sea turtle's herbivorous diet, paired with causes of reduced intestinal motility, may predispose the species to intestinal damage and subsequent obstructive intestinal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…The decreased exposure to the outdoors and other microbe-rich locations together with the increased indoor lifestyles (working and living) and obsessive cleaning habits that characterize Western culture today have led to the formulation of the hygiene hypothesis ( 27 ), which posits that a lack of exposure to beneficial microbes present in the environment leads to the increase in disease that we have seen in the past century. Captive animals, which live in enclosed environments not equivalent to their normal environments in the wild, experience diseases that are associated with or worsened by the captive environment, including gastric ulcers (vervet monkeys [ 28 ]), intestinal stricture (green sea turtles [ 29 ]), and end-stage renal disease (polar bears [ 30 ]). As we and others have shown, human houses and Komodo dragon zoo enclosures represent closed locations characterized by possibly circular microbial sharing with less microbial input from outside environments than that received by animals and humans living and working predominantly outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased exposure to the outdoors and other microbe-rich locations together with the increased indoor lifestyles (working and living) and obsessive cleaning habits that characterize Western culture today have led to the formulation of the hygiene hypothesis ( 27 ), which posits that a lack of exposure to beneficial microbes present in the environment leads to the increase in disease that we have seen in the past century. Captive animals, which live in enclosed environments not equivalent to their normal environments in the wild, experience diseases that are associated with or worsened by the captive environment, including gastric ulcers (vervet monkeys [ 28 ]), intestinal stricture (green sea turtles [ 29 ]), and end-stage renal disease (polar bears [ 30 ]). As we and others have shown, human houses and Komodo dragon zoo enclosures represent closed locations characterized by possibly circular microbial sharing with less microbial input from outside environments than that received by animals and humans living and working predominantly outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…Sea turtle cloacoscopy allows the view of different apparatuses, such the gastrointestinal, reproductive, and urinary, and if an accessible foreign body is present, it allows a minimally invasive removal, similar to esophagoscopy (Pressler et al 2003). Recently, diagnostic cloacoscopy in sea turtles was performed by Erlacher-Reid et al (2013) in order to diagnose the intestinal stricture in six green sea turtles (Chelonia mydas). To the authors' knowledge, no cloacoscopy study of loggerhead sea turtles has been found in veterinary literature.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, radiography can sometimes provide a noninvasive way to investigate diet (Schumacher and Toal, 2001;Erlacher-Reid et al, 2013;Beckmann et al, 2015). Mineral opaque material in the gastrointestinal tract is apparent in several of the iguanas (Figures 1a,b).…”
Section: Anatomical Observationsmentioning
confidence: 99%
“…Radiography is an established and clinically important way to assess bone integrity and health through the visualization of bones and internal organs (Mitchell, 2002;Banzato et al, 2013;Thrall, 2018), and can also sometimes be used to non-invasively investigate diet (Banzato et al, 2013;Erlacher-Reid et al, 2013;Beckmann et al, 2015). Despite these advantages, the large size of conventional radiography equipment has typically precluded imaging live marine vertebrates in the field.…”
Section: Introductionmentioning
confidence: 99%